(untitled) (International Journal of Geoscience, Engineering and Technology, 2022)
An overview of the work environment is necessary to identify the risk conditions of work to the safety of accidents, from these, as their functions will have significant criteria to social ones. This article presents the risk map implemented in a Civil Engineering laboratory at the Institute of Science, Engineering and Technology – ICET – at UFVJM. For that, a critical analysis was carried out based on the knowledge acquired in the Hygiene and Safety at work discipline, in the auxiliary bibliographies and in the information collected during the visit and mapping of the place. After collecting the data, it was possible to create a risk map, where the physical, chemical, ergonomic and accident analysis risks are justified. The map is the first prevention of What can be adjusted and the adjustment conditions of the environment.